Medicines containing allergen extract as an active substance - current quality requirements - Žigić, Gordana; Džunić, Ivana (Archives of Pharmacy, 2022)
Allergen products have increasing importance in recent years. The aim of this study is to present the newest quality regulatory requirements for these products. Searching the current regulation a review on specific quality control and manufacturing process requirements is presented. The Ph.Eur. monograph for Allergen products (01/2022:1063) with allergens of natural (biological) origin, defines specific quality control and manufacturing process requirements. The main parameters for quality verification include identification (protein profile and allergen profile), determination of protein content, total allergenic activity, and relevant individual allergens. Production phases can have a significant impact on product quality and must be adequately controlled. Also, the choice of source material of biological origin is important, which must be of prescribed quality and adequately qualified, and collection or production, and handling of source material must ensure a consistent batch composition. Further challenges include the selection of suitable raw materials (e.g. extraction solvents) and the in-house reference preparation for quality control and batch consistency verification, and its analytical characterization. When considering the quality of allergen products, it is necessary to take into account the relevant ICH and EMA guidelines, and WHO Database on the nomenclature and main characteristics of allergens. Compliance of allergen products with the current quality regulatory requirements is crucial in order that a product of controlled and consistent quality is supplied to patients, especially regarding the complex composition of the biological source material and significant variability in biological activity or content of relevant allergens that may occur in different batches of a medicine.